Content teachers’ and lecturers’ corrective feedback in EMI classes in high school and university settings - Hong, Jiye (Studies in Second Language Learning and Teaching, 2023)
To date, very limited research interest has been given to the strategies English-medium instruction (EMI) teachers or lecturers deploy to provide corrective feedback (CF) on the language use to their students during class interaction. In other words, when EMI teachers incidentally focus on students’ problematic language use, how do they correct it – providing explicit correction or using recast or elicitation? This article reports on a study that examined CF types EMI teachers and lecturers used during classroom discourse, drawing on data collected from classroom observations and recordings of six different EMI classes in high school and university settings in Korea. The frequency and types of CF used in reactive language-related episodes (LREs) were identified in the EMI classes and compared between the two settings and across disciplines (social science, mathematics, and computer science). Findings showed that all the EMI teachers and lecturers offered CF to their students but with different frequency; the schoolteachers offered CF more frequently than the university lecturers. Also, the schoolteachers used more various types of CF than the lecturers. In both settings, CF occurred most frequently in mathematics compared to the other two disciplines. This article ends with suggestions for ways the findings of this study can be used to raise EMI teachers’ awareness of various options for providing CF on students’ linguistic errors during their incidental teaching practices.